Manajemen Pendidikan Karakter pada Sekolah Dasar Penggerak Kecamatan Amahai Kabupaten Maluku Tengah - Sapulette, Frida; Ratumanan, T.G.; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research was motivated by the lack of optimal implementation of character education at driving elementary schools in Amahai sub-district. This is because the role of teachers in instilling the concept of character education tends to be less than optimal, there is still a lack of opportunities given to teachers to develop their potential in character education, the existence of external school factors, and the lack of supervision patterns in the implementation of character education. The aim of this research is to analyze the planning, organization, implementation, supervision and evaluation of character education management at the Driving Elementary School in Amahai District, Central Maluku Regency. This type of research is field research, using a qualitative research approach to analyze and describe the management of character education at driving elementary schools in Amahai sub-district. The research took place at 2 driving elementary schools in Amahai sub-district, in February-April 2023. This research data was obtained using observation, interviews and documentation techniques. Data analysis uses the Miles and Huberman method. Based on the results of the research, conclusions that can be given regarding the management of character education at the Driving elementary school in Amahai District are: (1) Planning begins with a program planning meeting at the beginning of the year which involves all school components. (2) Organizing is carried out by all teachers without being based on a Decree from the school principal. (3) Implementation is carried out in an integrative manner by all teachers including the school principal. (4) Supervision and evaluation are carried out by the internal supervisor, namely the Principal. (5) Character values in the dimensions of the Pancasila student profile which are characteristic, namely national morals, morals towards nature, mutual cooperation and religious morals. (6) Inhibiting and supporting factors are internal and external.